Seroprevalence of Hepatitis B among blood donors in Jhapa, Nepal - Khanal, H; Bhatta, DR; Tiwari, BR; Joshi, DR (Sunsari Technical College Journal, 2013)
Background: Blood donation saves life of millions. However unsafe transfusion is also putting blood receivers in risk of Hepatitis B infections and window period is potential cause of transmission. Objectives: The objective of the study was to find out the seroprevalence of hepatitis B among blood donors. Materials and Methods: During the study period from July 2008 to April 2009, a total of 2277 donated blood samples from Nepal Red Cross Society Jhapa Branch and Damak Sub-branch were analyzed for present of hepatitis B surface antigen (HBsAg) on serum by using Hepacard, a rapid diagnostic chromatographic test kit. Results: On the study HBsAg seroprevalence were 7 out of 1340 (0.52%) and 6 out of 937(0.64%) in Bhadrapur and Damak respectively. The Hepatitis B Virus (HBV) prevalence among male at Bhadrapur was found 7 out of 1172 (0.59%) and 6 at Damak out of 760 (0.79%) were positive. The overall seroprevalence of male blood donors in Jhapa district was 12 out of 1932 (0.62%). Among the 168 female blood donors only one female was seen positive at Bhadrapur with 0.59% of seroprevalence and overall seroprevalence of hepatitis B surface antigen among female in Jhapa district was 1 out of 345 (0.29%). Conclusion: Hepatitis B infection is a most important threat associated with unscreened blood donations. It.s a great importance to perform and confirm donated blood by sensitive and specific tests. It is essential to prevent the transmission of hepatitis B virus from blood donors. DOI: http://dx.doi.org/10.3126/stcj.v1i1.8659 Sunsari Technical College Journal Vol.1(1) 2012 33-37